2019
DOI: 10.1002/slct.201902533
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Nanocellulose from Broomcorn Stalks and Its Application for Nanocellulose/Xanthan Film Preparation

Abstract: Nanocellulose extraction from broomcorn stalk was conducted using acid hydrolysis followed by sonication. The influence of acid concentration, hydrolysis time and temperature on nanocellulose isolation was studied. The minimum size and maximum yield of isolated nanocellulose were 40 nm and 71%, respectively obtained at acid concentration of 45 wt%, temperature of 45 °C and time of 75 min. The isolated nanocellulose was characterized through dynamic light scattering, Fourier transform infrared spectroscopy, fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Filter paper and microcrystalline cellulose Solution plasma-chemical processing as an oxidation-hydrolysis strategy Surov et al, 2018 Cotton linters Single step ammonium persulfate-assisted swelling, followed by oxidation Wang et al, 2019 Cellulose fibers Ball mill assisted fully recyclable solid acid hydrolysis Song et al, 2018 Broomcorn Stalks Acid hydrolysis followed by sonication Langari et al, 2019 Eucalyptus hardwood Irradiation oxidation and organosolv solubilization Zhang and Liu, 2018 Microcrystalline cellulose Ultrasonic pretreatment in ionic liquid followed by acid hydrolysis Pang et al, 2018 Nata de coco Ultrasonic irradiation coupled with microwave treatment Wardhono et al, 2018 Oil palm Sono-assisted TEMPO oxidation Rohaizu and Wanrosli, 2017 Wood sawdust Sono-chemical synthesis using acid hydrolysis Shaheen and Emam, 2018 Microcrystalline cellulose Recyclable citric/hydrochloric acids Yu et al, 2019 Commercial microcrystalline cellulose…”
Section: Natural Source Methodology Referencesmentioning
confidence: 99%
“…Filter paper and microcrystalline cellulose Solution plasma-chemical processing as an oxidation-hydrolysis strategy Surov et al, 2018 Cotton linters Single step ammonium persulfate-assisted swelling, followed by oxidation Wang et al, 2019 Cellulose fibers Ball mill assisted fully recyclable solid acid hydrolysis Song et al, 2018 Broomcorn Stalks Acid hydrolysis followed by sonication Langari et al, 2019 Eucalyptus hardwood Irradiation oxidation and organosolv solubilization Zhang and Liu, 2018 Microcrystalline cellulose Ultrasonic pretreatment in ionic liquid followed by acid hydrolysis Pang et al, 2018 Nata de coco Ultrasonic irradiation coupled with microwave treatment Wardhono et al, 2018 Oil palm Sono-assisted TEMPO oxidation Rohaizu and Wanrosli, 2017 Wood sawdust Sono-chemical synthesis using acid hydrolysis Shaheen and Emam, 2018 Microcrystalline cellulose Recyclable citric/hydrochloric acids Yu et al, 2019 Commercial microcrystalline cellulose…”
Section: Natural Source Methodology Referencesmentioning
confidence: 99%
“…For the dry 3D matrix, we prepared thin films of MCC-OH and xanthan gum (XG) by way of solvent casting, adding glycerol as a plasticizing agent. Xanthan gum has been widely explored in the literature as a biocompatible and sustainable biomaterial for the production of thin films, whereas MCC has been blended with several polysaccharides to act as a reinforcing agent [ 29 , 30 , 31 ]. Furthermore, glycerol has been extensively investigated as a biocompatible plasticizer for biomaterial-based thin films and hydrogels [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…2. The broadbands observed at 3408 cm −1 in all samples belong to the stretching vibration of O-H and the peak at 1646 cm −1 is attributed to the absorbed water molecules by the samples (Langari et al 2019). These peaks show the hydrophilic tendency of all samples.…”
Section: Ftir Analysismentioning
confidence: 88%
“…In this study, the NC was isolated from BS according to the methodology reported in our previous study (Langari et al 2019). To remove non-cellulosic components (hemicellulose and lignin), the BS powder was subjected to alkali pretreatment and bleaching, as described in details in our previous study (Langari et al 2019). The bleached BS (BBS) was subjected to acid hydrolysis.…”
Section: Isolation Of Nanocellulose From Bsmentioning
confidence: 99%